Implementasi Pembelajaran Seni Tari Tradisional Gandrung dalam Upaya Meningkatkan Kecerdasan Kinestetik pada Anak Usia 5-6 Tahun Di Era Perwanida II Purwosari - Hurun Aini; Riris Wahyuningsih; Jon Iskandar Bahari (Journal of Islamic Education for Early Childhood, 2021)
This study aims to describe: 1) Implementation of learning the art of traditional gandrung dance in an effort to improve the kinesthetic intelligence of children aged 5-6 years, 2) Supporting and inhibiting factors in the implementation of learning gandrung traditional dance in an effort to improve the kinesthetic intelligence of children aged 5-6 years in RA Perwanida II Purwoasri Tegaldlimo. This type of research uses qualitative research methods with research subjects principals, teachers, parents, and students aged 5-6 years at RA Perwanida II Tegaldlimo. Data was collected using the methods of observation, interviews, and documentation. In conducting this research, the researcher is the main instrument assisted by observation, interviews, and documentation. Data analysis in this study is data reduction, data presentation, and drawing conclusions. Triangulation is carried out to explain the validity of the data using source triangulation. The results of this study indicate that: 1) The implementation of learning the art of traditional gandrung dance in an effort to improve the kinesthetic intelligence of children aged 5-6 years, based on initial observations it is known that out of 14 children 5 developed as expected and 9 children began to develop, and after the research showed results that the kinesthetic intelligence of 14 children aged 5-6 years, 9 children developed very well, 2 children developed as expected and 3 children began to develop. 2) supporting factors, teacher readiness, support from parents, as well as talents that support and inhibit factors, teachers are less than optimal in providing material, lack of teacher preparation, and lack of support from parents.